Penerapan Model Problem Based Learning (PBL) untuk Meningkatkan Kajian Hasil Belajar IPA Pada Tema 2 di Kelas IV SD Dian Andalas Kota Padang - Putri, Diana; Arlis, Syamsu; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The background of this research is that science learning outcomes are still low. This condition is caused when the learning process takes place the teacher has not oriented students towards the problem, less guiding students in doing the task and evaluating the task given. The puspose of reseacrh is describe science learning using the Problem Based Learning (PBL) model in fourth grade students at Dian Andalas Elementary School Padang. This type of research is classroom action research with qualitative and quantitative approaches. The study consisted of two cycles of Iitus cycle I and cycle II. Data collection techniques in the form of observation and tests. This research includes (1) planning, (2) implementation, (3) observation, (4) reflection. The research subjects were teachers and fourth grade students of Dian Andalas Elementary School, amounting to 20 people consisting of 7 women and 13 men. The results of the study showed that planning, implementation and student learning outcomes had increased. The assessment of RPP of the first cycle of meeting 1 averaged 67.85% of qualifications sufficient, meeting 2 averaged 78.57% with good qualifications. in the second cycle an average of 92.85% with very good qualifications. Furthermore the learning process carried out is in accordance with the steps of implementing the PBL model in the first cycle of meeting 1 having a percentage of teacher aspects 67.85% and student aspects 67.85%. In the first cycle of meeting 2 the percentage of teacher aspects was 82.14% and student aspects were 78.57%. The first cycle experienced an increase in the second cycle which had a percentage of teacher aspects and student aspects 92.85%. Thus it can be concluded that science learning using the Problem Based Learning (PBL) model can improve student learning outcomes in elementary schools.